2016
DOI: 10.1073/pnas.1517027113
|View full text |Cite
|
Sign up to set email alerts
|

Core disgust is attenuated by ingroup relations

Abstract: We present the first experimental evidence to our knowledge that ingroup relations attenuate core disgust and that this helps explain the ability of groups to coact. In study 1, 45 student participants smelled a sweaty t-shirt bearing the logo of another university, with either their student identity (ingroup condition), their specific university identity (outgroup condition), or their personal identity (interpersonal condition) made salient. Self-reported disgust was lower in the ingroup condition than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 29 publications
(24 reference statements)
3
80
0
1
Order By: Relevance
“…326). Indeed, recent work has provided experimental evidence of the role of disgust in mediating the relationship between group identity and avoidance (Reicher, Templeton, Neville, Ferrari, & Drury, 2016). Specifically, in this research, after smelling a sweaty T-shirt, disgust-measured by either self-report or an unobtrusive measure of walking time to wash hands or number of pumps of hand sanitizer used-was lower when participants believed the T-shirt was owned by a member of their own group.…”
Section: Evolutionary Sourcesmentioning
confidence: 84%
“…326). Indeed, recent work has provided experimental evidence of the role of disgust in mediating the relationship between group identity and avoidance (Reicher, Templeton, Neville, Ferrari, & Drury, 2016). Specifically, in this research, after smelling a sweaty T-shirt, disgust-measured by either self-report or an unobtrusive measure of walking time to wash hands or number of pumps of hand sanitizer used-was lower when participants believed the T-shirt was owned by a member of their own group.…”
Section: Evolutionary Sourcesmentioning
confidence: 84%
“…Indeed we even have evidence that noises attributed to the Mela, and hence seen as identity relevant, are encoded more richly and remembered better than identical noises attributed to non-identity relevant sources (Srinivasan, et al, 2013;Srinivasan, Tewari, Makwana, & Hopkins, 2015). Finally, as concerns the issue of proximity and the experience of disgust, we have evidence from elsewhere that bodily excreta (sweat in this case) are experienced as less disgusting when they emanate from an ingroup source (Reicher, Templeton, Neville, Ferrari & Drury, 2016) All in all, and across a series of modalities, we see that the identity relevance of stimuli -that is, precisely what they mean in relation to the self and whether they affirm or undermine the self, is critical to the way that they are encoded, evaluated and approached (or else avoided). Indeed, we even have evidence from very different settings (the Kosovan war)…”
Section: Exploring the Dynamics Of The Variable Selfmentioning
confidence: 61%
“…Here the category is about creating reality rather than reflecting reality. It is about creating a constituency of people acting together and hence (as we have previously argued) having the power to bring new forms of social organisation into being (Reicher & Hopkins, 2001). Another way of putting this is to say that social identity processes are oriented to the future not just the present.…”
Section: From Perception To Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the liking and morality judgments, previous research have shown that these could be influenced by aversive odors (Alaoui-Ismaili, Robin, Rada, Dittmar, & Vernet-Maury, 1997;Croy, Olgun, & Joraschky, 2011;Herz, Schankler, & Beland, 2004;Kirk-Smith, Van Toller, & Dodd, 1983;Reicher, Templeton, Neville, Ferrari, & Drury, 2016;Rozin & Fallon, 1987;Schnall, Haidt, Clore, & Jordan, 2008;Stevenson, 2010;Yeshurun & Sobel, 2010), but whether odor evaluative conditioning would similarly shape morality and liking judgments is unclear.…”
Section: Introductionmentioning
confidence: 99%